Agricultural innovation system: analysis from the subsystems of R&D, training, extension, and sustainability - Gutiérrez Cano, Luis Fernando; Zartha Sossa, Jhon Wilder; Orozco Mendoza, Gina Lía; Suárez Guzmán, Lina María; Agudelo Tapasco, Diego Alejandro; Quintero Saavedra, Jorge Iván (Frontiers in Sustainable Food Systems, 2023)
The challenges faced by agricultural innovation systems (A.I.S) are complex to solve, however, the authors consider that understanding the processes of innovation and development (R&D), sustainability, the use of ICTs, training, and outreach as the focus of discussion in this review-have great potential for closing the gaps in the system; likewise, the consideration of strategies, projects and best practices that dynamize the operation of the system. The objective of this article is to review the literature about A.I.S. A to identify its obstacles, challenges, and the solution to its closing of gaps. The methodology identifies the critical system monitoring factors and defines search suitability for obtaining 55 documents. With the results a qualitative analysis on the axes mentioned, which is complemented with Vantage Point V 15.1 text mining software to graphically observe the most relevant aspects. Within the conclusions is a constant demand from actors the access to information, and knowledge in the training processes, it is recommended in this regard the additional skills for innovation and participation in concerted practices. Concerning the limitations of agricultural innovation processes, it suggests the incorporation of cooperatives, technological platforms, and farmers' organizations as intermediaries relevant to the closing of gaps. As for sustainability, A.I.S. thinking is recommended for inclusive dialogue among actors and to facilitate transitions to sustainability. Finally, to overcome the sociotechnical and ethical challenges for access to technologies and technological transition, it is recommended the formulation of appropriate policies for access to resources and the development of markets that enhance business opportunities and the development of sustainable innovations.